TECHNOLOGY ADOPTION AND THE ROLE OF GOVERNMENT IN ENSURING THE SUSTAINABILITY OF MICRO, SMALL AND MEDIUM ENTERPRISES IN BANDA ACEH CITY - Riyaldi, Muhammad Haris; Teuku Muhammad Syahrizal; Muhammad Hafidh (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
The micro, small and medium enterprise (MSME) sector has become one of the significant drivers of economic development, job creation, and poverty alleviation. Government attention needs to be given as an important path for the progress of the community's economy so that their business performance has a positive impact on the sustainability of their business. In an era of rapid technological development, technology adoption is a necessity for business actors so that business growth and performance can be improved. Business expansion, competitive advantage, and consumer satisfaction can be improved by adopting technology. Further research needs to be carried out in order to analyze the development and sustainability of MSMEs by considering the contribution of government support and technology adoption. The strength of the MSME sector can support the community's economy so that the rate of economic growth and welfare levels increase. The results of this study can answer the challenge of the government's role in optimizing the progress of the MSME sector in Banda Aceh City.